Talk to me! Examining parent-coach communication frequency and satisfaction in youth soccer - Eckardt, V. C.; Pallares Herbeck, M.; Hufer, D.; Schwab, S. (International Journal of Sport and Exercise Psychology, 2025)
Regular and honest communication can enhance trust and facilitate cooperation between parents and coaches in youth sport. Given the significance of positive parent-coach interactions for athletes' development and sport-related outcomes, parents' and coaches' use of communication in day-to-day activities warrants increased scientific attention. This study sought to assess the frequency, perceived effectiveness, and perceived satisfaction of digital and non-digital communication modes between parents and coaches in youth soccer. To meet that objective, a quantitative online survey was administered to parents (N = 1024) and coaches (N = 340) in amateur and elite youth soccer to understand perceptions of mutual communication. Results showed that parents perceived communication frequency to be significantly lower across modes (i.e., regular conversations after practice/competitions, phone calls) compared to coaches. Further, WhatsApp groups were the most frequently implemented but not the most effective mode of communication for both parents and coaches on a weekly basis. In general, the majority of parents indicated to be satisfied with contemporary parent-coach communication which significantly contributed to a positive perception of overall parent-coach cooperation. Findings will be discussed within the light of potential implications for the use of communication strategies in coaching, coach education, as well as organisational decision making in youth sport.